1992
DOI: 10.1073/pnas.89.7.3075
|View full text |Cite
|
Sign up to set email alerts
|

Independent domain folding of Pseudomonas exotoxin and single-chain immunotoxins: influence of interdomain connections.

Abstract: We have studied the refolding of completely unfolded and reduced Pseudomonas exotoxin (PE) and of recombinant single-chain immunotoxins made with monoclonal antibody B3 that are composed of a heavy-chain variable region connected by a flexible linker to the corresponding light-chain variable region (Fv), which is in turn fused to a truncated form of PE. We have found by direct activity assays that different functional domains of these multf onal proteins fold independently with different kinetics. The ADPribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
2

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 32 publications
3
46
0
2
Order By: Relevance
“…ARGININE was first used in refolding of human tissue type plasminogen activator [18,19]. Since then, it has been used for refolding of a variety of proteins including casein kinase II, [20], Fab antibody fragments [18,21], growth hormone [22], human gamma interferon, [23], human matrix metalloproteinase-7 human neurotrophins [24] human p53 tumor suppressor protein [25], interleukin-21 [26], interleukin-6 receptor [27], lysozyme [28], single-chain Fv fragments [29], and singlechain immunotoxins [18,30]. However, arginine may act as a protein-denaturant, which limits the expansion of its applications.…”
Section: Arginine (Arg)mentioning
confidence: 99%
“…ARGININE was first used in refolding of human tissue type plasminogen activator [18,19]. Since then, it has been used for refolding of a variety of proteins including casein kinase II, [20], Fab antibody fragments [18,21], growth hormone [22], human gamma interferon, [23], human matrix metalloproteinase-7 human neurotrophins [24] human p53 tumor suppressor protein [25], interleukin-21 [26], interleukin-6 receptor [27], lysozyme [28], single-chain Fv fragments [29], and singlechain immunotoxins [18,30]. However, arginine may act as a protein-denaturant, which limits the expansion of its applications.…”
Section: Arginine (Arg)mentioning
confidence: 99%
“…The final modification of the scFv-BSRNase fusion protein constructs was the inclusion of a spacer/linker sequence between the scFv and the BSRNase. This was added to separate further the two portions of the molecule to allow better independent folding (as observed for Pseudomonas exotoxin immunotoxins ;Brinkmann et al, 1992). In addition, it has been shown that the N-termini of the BSRNase dimer are exchanged across the subunit interface in some forms of the dimer .…”
Section: Enzyme-linked Immunosorbent Assays and Western Blotsmentioning
confidence: 99%
“…It has been reported that transforming growth factor a, IL2, IL3, IL4, IL6, GM-CSF, and insulin-like growth factor I all bind with 20-to 250-fold reduced affinity after fusion to another protein (7,(13)(14)(15)(16). Previously, the options available for improving the function of a fusion protein were limited to switching the order of the two proteins, attaching linkers in between the two proteins, or mutating one of the proteins to decrease junctional effects (13,17).…”
mentioning
confidence: 99%